The microbiota–gut–brain axis in mental and neurodegenerative disorders: opportunities for prevention and intervention - Yassin, Lidya K.; Skrabulyte-Barbulescu, Jurga; Alshamsi, Shamsa H.; Saeed, Sara; Alkuwaiti, Shamma H.; Almazrouei, Saif; Alnuaimi, Abeer; BaniYas, Shamsa; Aldhaheri, Dana; Alderei, Mahra; Shehab, Safa; Hamad, Mohammad I. K. (Frontiers in Aging Neuroscience, 2025)
The microbiota–gut–brain axis (MGBA) is increasingly recognized as a critical regulator of brain health, influencing both neurodevelopment and age-related neurological decline. Disruptions in this axis, driven by gut dysbiosis, have been implicated in the pathogenesis of a wide range of neurodegenerative and neuropsychiatric disorders. This review synthesizes current evidence linking microbiota alterations to Alzheimer's disease (AD), Parkinson's disease (PD), amyotrophic lateral sclerosis (ALS), multiple sclerosis (MS), and stroke—including post-stroke cognitive impairment (PSCI), as well as major depressive disorder (MDD), bipolar disorder (BD), anxiety disorders, post-traumatic stress disorder (PTSD), and chronic fatigue syndrome (CFS). Common findings include reduced microbial diversity, depletion of short-chain fatty acid (SCFA)-producing genera, and enrichment of pro-inflammatory taxa. These changes contribute to neuroinflammation, blood–brain barrier (BBB) dysfunction, microglial activation, and neurotransmitter imbalances. The review further explores the neurotoxic effects of external factors such as radiation and xenobiotics on the MGBA. Despite disorder-specific variations, shared microbial and immunological mechanisms emerge across the spectrum of conditions. Importantly, we present current and emerging strategies aimed at restoring gut–brain communication, including dietary interventions such as fiber-rich and Mediterranean diets, SCFA supplementation, probiotics, and fecal microbiota transplantation (FMT). These approaches show promise in alleviating cognitive and emotional symptoms, modulating immune responses, and potentially slowing disease progression. By integrating mechanistic insights with therapeutic perspectives, this review underscores the gut microbiota as a modifiable factor in neuropsychiatric and neurodegenerative disease. Targeting the MGBA offers a novel, translational approach to intervention that may ultimately contribute to healthier brain aging and improved outcomes across the lifespan.